195k views
3 votes
Solve the system of equations -x-y=-4−x−y=−4 and -2x+4y=4−2x+4y=4 by combining the equations.

1 Answer

3 votes

9514 1404 393

Answer:

(x, y) = (2, 2)

Explanation:

We can put the second equation into standard form by dividing by -2.

x -2y = -2

Adding this to the first equation eliminates x

(x -2y) +(-x -y) = (-2) +(-4)

-3y = -6

y = 2 . . . . . divide by -3

-x -(2) = -4 . . . . substitute for x in the first equation

2 = x . . . . . . . . add 4+x

The solution is (x, y) = (2, 2).

User Sumit Pandey
by
4.5k points